2020
DOI: 10.1038/s41598-020-70618-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of small RNA populations generated in peanut leaves after exogenous application of dsRNA and dsDNA targeting aflatoxin synthesis genes

Abstract: Previously, we have shown that RNA interference (RNAi) can prevent aflatoxin accumulation in transformed peanuts. To explore aflatoxin control by exogenous delivery of double-strand RNA (dsRNA) it is necessary to understand the generation of small RNA (sRNA) populations. We sequenced 12 duplicate sRNA libraries of in-vitro-grown peanut plants, 24 and 48 h after exogenous application of five gene fragments (RNAi-5x) related to aflatoxin biosynthesis in Aspergillus flavus. RNAi-5x was applied either as double-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Table 3, showed that exogenous application is effective in suppressing fungal growth. For example, a recent study by Werner and colleagues [38] showed that using spray-induced gene silencing The exogenous application of dsRNA can be very interesting also on horticultural produces at the postharvest stage [11] and against fungal pathogens, which are capable of producing mycotoxins very harmful to animal and human health [101,102]. Their control at the disposition stage is strictly limited to a few active ingredients due to residue concerns.…”
Section: Delivery Methodsmentioning
confidence: 99%
“…Table 3, showed that exogenous application is effective in suppressing fungal growth. For example, a recent study by Werner and colleagues [38] showed that using spray-induced gene silencing The exogenous application of dsRNA can be very interesting also on horticultural produces at the postharvest stage [11] and against fungal pathogens, which are capable of producing mycotoxins very harmful to animal and human health [101,102]. Their control at the disposition stage is strictly limited to a few active ingredients due to residue concerns.…”
Section: Delivery Methodsmentioning
confidence: 99%
“…Not surprisingly, a wide spectrum of RNA interference based technologies has been developed and tested in planta to control AF production by aflatoxigenic fungi ( McDonald et al, 2005 ; Majumdar et al, 2017 ; Wu, 2022 ). A frequently targeted gene is aflR in both peanut ( Arias et al, 2015 ; Faustinelli et al, 2018 ; Power et al, 2020 ) and maize ( Masanga et al, 2015 ). Other approaches targeted either the aflS regulatory gene ( Arias et al, 2015 ; Power et al, 2020 ) or AF biosynthetic genes including aflC (encoding polyketide synthase; Arias et al, 2015 ; Thakare et al, 2017 ; Power et al, 2020 ; Niño-Sánchez et al, 2021 ) and aflM (coding for versicolorin dehydrogenase; Raruang et al, 2020 ).…”
Section: Genetics Of Aflatoxin Productionmentioning
confidence: 99%
“…A frequently targeted gene is aflR in both peanut ( Arias et al, 2015 ; Faustinelli et al, 2018 ; Power et al, 2020 ) and maize ( Masanga et al, 2015 ). Other approaches targeted either the aflS regulatory gene ( Arias et al, 2015 ; Power et al, 2020 ) or AF biosynthetic genes including aflC (encoding polyketide synthase; Arias et al, 2015 ; Thakare et al, 2017 ; Power et al, 2020 ; Niño-Sánchez et al, 2021 ) and aflM (coding for versicolorin dehydrogenase; Raruang et al, 2020 ). It is noteworthy that a RNAi-based AF control system simultaneously silencing aflR , aflR , aflC , aflep (coding for AF efflux pump) and pes1 (encoding a non-ribosomal peptide synthase with hypothesized function in cyclopiazonic acid biosynthesis) was also constructed and tested in peanut using both transgenic and non-transgenic delivery tools ( Arias et al, 2015 ; Power et al, 2020 ).…”
Section: Genetics Of Aflatoxin Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exogenous application of dsRNA can be very interesting also on horticultural produces at the postharvest stage [ 11 ] and against fungal pathogens, which are capable of producing mycotoxins very harmful to animal and human health [ 44 , 160 ]. Their control at the disposition stage is strictly limited to a few active ingredients due to residue concerns.…”
Section: Exogenous Delivery Of Small Rna For Controlling Fungal Pathogens Of Plantsmentioning
confidence: 99%